Decomposição de elastômeros por combustão iniciada por microondas em sistema fechado - Moraes, Diogo Pompéu de (2006)
A rapid digestion procedure for further determination of inorganic elements in carbon black-containing elastomers has been developed using sample combustion in closed quartz vessels with oxygen pressure. Microwave radiation was used for the ignition step. Samples containing high levels of carbon black (up to 30%) were digested using the proposed procedure: nitrile-butadiene rubber (NBR) and ethylenepropylene-diene monomer (EPDM). A quartz device was used simultaneously as a sample holder and for the protection of vessel cap. Sample was pressed as pellet and placed together a small piece of low-ash content paper in the holder. Ammonium nitrate solution (50 ml of 50% m/v) was added to the paper as aid for ignition. The influence of the absorption solution (nitric acid or water) and the necessity of an additional reflux step were evaluated. Determination of Al, Fe, Mn, Sr and Zn was performed by inductively coupled plasma optical emission spectrometry. A reference method (ASTM D 4004-064) based on conventional dry ashing followed by flame atomic absorption spectrometry determination was used for results comparison (Mn and Zn). Results were also compared to those obtained by using wet acid digestion in closed systems. As no certified reference elastomers were available analyte spikes were made for NBR and EPDM digests. Concentrated and diluted (4 mol l-1) nitric acid, with 5 min for reflux step after the combustion process, gave better recoveries for all analytes (from 97 to 101%). For Al and Mn recoveries were bellow 90% for both open and closed vessels using HNO3 and H2SO4 mixture. For dry ashing quantitative recoveries were found only for Zn (for Al recovery was 14%). Residual carbon content was bellow 0.5% for the proposed procedure. With the proposed procedure further determination of Al, Mn, Sr and Zn is feasible with only the combustion step but for Fe a reflux with diluted HNO3 was necessary. Then, using the proposed procedure complete sample digestion is obtained is less time than other procedures and no need of concentrated acids was considered necessary.